Chromatin Landscape Dynamics in the Early Development of the Plant Parasitic Nematode Meloidogyne incognita - Hassanaly-Goulamhoussen, Rahim; De Carvalho Augusto, Ronaldo; Marteu-Garello, Nathalie; Péré, Arthur; Favery, Bruno; Da Rocha, Martine; Danchin, Etienne G. J.; Abad, Pierre; Grunau, Christoph; Perfus-Barbeoch, Laetitia (Frontiers in Cell and Developmental Biology, 2021)
In model organisms, epigenome dynamics underlies a plethora of biological processes. The role of epigenetic modifications in development and parasitism in nematode pests remains unknown. The root-knot nematode Meloidogyne incognita adapts rapidly to unfavorable conditions, despite its asexual reproduction. However, the mechanisms underlying this remarkable plasticity and their potential impact on gene expression remain unknown. This study provides the first insight into contribution of epigenetic mechanisms to this plasticity, by studying histone modifications in M. incognita. The distribution of five histone modifications revealed the existence of strong epigenetic signatures, similar to those found in the model nematode Caenorhabditis elegans. We investigated their impact on chromatin structure and their distribution relative to transposable elements (TE) loci. We assessed the influence of the chromatin landscape on gene expression at two developmental stages: eggs, and pre-parasitic juveniles. H3K4me3 histone modification was strongly correlated with high levels of expression for protein-coding genes implicated in stage-specific processes during M. incognita development. We provided new insights in the dynamic regulation of parasitism genes kept under histone modifications silencing. In this pioneering study, we establish a comprehensive framework for the importance of epigenetic mechanisms in the regulation of the genome expression and its stability in plant-parasitic nematodes.